1999
DOI: 10.1002/(sici)1097-4628(19990711)73:2<295::aid-app16>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Nylon 6 by phenol-containing polymers

Abstract: A crystalline polymer, Nylon 6, was selectively blended with various amorphous polymers containing phenolic moieties. It was found that moisture absorption by the amide group in Nylon 6 could effectively be reduced by blending with p-Cl-novolac at ratios as low as 2 phr (part per hundred resin). Blends of Nylon 6 with vinylphenol homopolymer and its copolymer with styrene also showed reduced moisture uptakes, but the effect was less dramatic than that of the p-Cl-novolac blend at all blend ratios. Novolac cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…One effective way to decrease the moisture content of nylon materials is to reduce their amide groups. For example, Huang et al successfully limited the moisture absorption of nylon-6 by blending it with vinyl phenol that was categorized as hydrogen bond donors [10]. On the other hand, the high moisture contents of the MC nylon composites are due partly to the low degree of crystallinity (lower than 40%).…”
Section: Moisture Absorption Characteristic Of the Cf/mc Compositesmentioning
confidence: 99%
“…One effective way to decrease the moisture content of nylon materials is to reduce their amide groups. For example, Huang et al successfully limited the moisture absorption of nylon-6 by blending it with vinyl phenol that was categorized as hydrogen bond donors [10]. On the other hand, the high moisture contents of the MC nylon composites are due partly to the low degree of crystallinity (lower than 40%).…”
Section: Moisture Absorption Characteristic Of the Cf/mc Compositesmentioning
confidence: 99%
“…Various polymer blends have been proposed to improve the mechanical properties of PA6 under humid and high-temperature conditions. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Owing to the small mixing enthalpy of macromolecules, almost all polymer combinations are immiscible 5 and thus, previous studies have mainly conducted PA6 polymer blending with immiscible components. [7][8][9][10][11][12][13][14] Blending high-T g polymers, such as poly(phenylene sulde), 7,8 poly(phenylene oxide), [9][10][11] and polycarbonate (PC) [12][13][14] with PA6 are representative approaches to increase the PA6 stiffness at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phenol-containing polymers, such as phenol novolac (PN) and PA6 blends, have been reported as miscible systems. [15][16][17][18][19][20][21] PN forms strong hydrogen bonds with PA6, which contribute to the miscibility of such blends. 16,18 Miscible components can increase the T g of PA6, and we previously reported that high-molecular-weight PN efficiently increases the T g of PA6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there have been some more fundamental attempts, which are preventing water absorption and increasing the T g of PA6 by blending it with phenol-containing polymers such as phenol novolac (PN), 5 7 polyvinylphenol, 8 and their derivatives. 9 These polymers can form strong hydrogen bonds between the carbonyl groups of PA6 and the hydroxyl groups of phenol-containing polymers. Quantum mechanical calculations have shown that the hydrogen bonds between PA6 and phenol-containing polymers are stronger than the hydrogen bond between PA6 and water molecules.…”
Section: Introductionmentioning
confidence: 99%